Abraham's curse: child sacrifice in the legacies of the West; [the roots of violence in judaism, christianity, and islam] - Chilton, Bruce (Doubleday, 2008)
The test -- Sacrificial species, human offerings -- Jewish martyrdom -- Blood of the Lamb -- The Son's eternal sacrifice -- Martyrs, in the flesh -- Gnostic laughter, Roman pornography, blood payment -- Taking leave of Moriah -- Ibrahim's sacrificial vision -- Blood harvest -- The long descent